Endobronchial carcinoid tumor in a Crohn disease patient treated with a TNFα inhibitor - Carcano, Carolina; Oliveira, Eduardo C; Martinez, Felipe; Kirsch, Jacobo (Translational Lung Cancer Research; Vol 2, No 1 (February 14, 2013): Translational Lung Cancer Research, 2013)
A young patient with Crohn’s disease is presented in whom pulmonary carcinoid tumor was incidentally found. Bronchoscopy showed an endobronchial lesion and biopsy pathology was consistent with atypical carcinoid. Octeotride scan suggested primary origin of the tumor. Although patients with Crohn’s disease have been reported to have increased incidence of intestinal carcinoid, we believe this to be the second case of primary carcinoid pulmonary located in this population.